Aiaa Space 2016 2016
DOI: 10.2514/6.2016-5466
|View full text |Cite
|
Sign up to set email alerts
|

NASA's Public Participation Universe: Why and How the U.S. Space Agency Is Democratizing Its Approaches to Innovation

Abstract: This paper analyzes NASA's increasing effort to invite greater public participation in its technoscientific work through open innovation methodologies. First we examine why NASA has expanded its use of these approaches, noting the roles of an intertwined set of forcing functions including budget constraints, the growth of scientific data, availability of technological resources, political climate, and committed individuals. Next we outline the strategies the agency has invoked to engage the public in research,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Also during this time, 98% of the posted challenges resulted in cost savings for NASA, and approximately 90% of the challenges resulted in scheduled savings-increasing the speed, flexibility, and adaptability of NASA to new mission objectives. According to NASA leaders who implemented open innovation in the agency, 78 NASA has established a suite of initiatives, policies, funding streams, organizations, and communities aimed at facilitating the agency's use of "open innovation" approaches to engage members of the public in lending their skills, ideas, enthusiasm, and time to advance particular goals and objectives. NASA has welcomed a diverse set of individuals to collect and analyze scientific data, make discoveries, develop technologies and data applications, and solve complex problems.…”
Section: Incremental Change Initiative: the Center Of Excellence For ...mentioning
confidence: 99%
“…Also during this time, 98% of the posted challenges resulted in cost savings for NASA, and approximately 90% of the challenges resulted in scheduled savings-increasing the speed, flexibility, and adaptability of NASA to new mission objectives. According to NASA leaders who implemented open innovation in the agency, 78 NASA has established a suite of initiatives, policies, funding streams, organizations, and communities aimed at facilitating the agency's use of "open innovation" approaches to engage members of the public in lending their skills, ideas, enthusiasm, and time to advance particular goals and objectives. NASA has welcomed a diverse set of individuals to collect and analyze scientific data, make discoveries, develop technologies and data applications, and solve complex problems.…”
Section: Incremental Change Initiative: the Center Of Excellence For ...mentioning
confidence: 99%
“…From 2005 to 2015, Gustetic et al (2015) show that 50 NASA challenges produced various outcomes, including research advancement, NASA operational integration/use, external use for other agencies, education and public outreach, advancing state of the art and demonstrating proof of concept, enabling products to be brought to market, and creating new aerospace vendors and companies. Adopting complementary crowdsourcing allows NASA to coproduce with the public and to generate a broader range of solutions than would be possible with a contract with a single company (Kaminski et al, 2016).…”
Section: Varieties Of Crowdsourcing Casesmentioning
confidence: 99%
“…Solicited ideas from the prize competition complemented the mission of NASA and resolved issues related to data applications, hardware prototype development, and concepts for research and technology advancement (Kaminski et al, 2016). As an example, the Mapping Dark Matter Challenge aimed to create a cosmological image analysis program to measure the small distortion in galaxy images caused by dark matter.…”
Section: Varieties Of Crowdsourcing Casesmentioning
confidence: 99%
“…Research has demonstrated that prize competitions can yield a wide range of cross-disciplinary potential solutions to global problems. 23 NASA, for instance, has hosted approximately 400 competitions that have enabled the global public to use wide-ranging expertise and problem-solving strategies to generate innovative solutions to space utilization problems. 24 The Space Innovation Governance Contest sought to address pertinent questions, namely (1) how can dominant narratives of space governance be positively influenced by opinions of aspiring and relatively new space actors and (2) how can we best design a platform or forum that supports continual engagement by participations particularly African youth, a nontraditional source of ideas and knowledge used for the generation of space law and policy.…”
Section: Findings From Open Innovationmentioning
confidence: 99%